HIFs genes expression and hematology indices responses to different oxygen treatments in an ovoviviparous teleost species Sebastes schlegelii. (September 2015) - Mu, Weijie; Wen, Haishen; Li, Jifang; He, Feng
Abstract: Hypoxia-inducible factors (HIFs) are transcription factors considered as a respond factor to oxygen tension. By using quantitative real-time PCR, expression files of HIF-1α and HIF-2α mRNA were detected in the Korean rockfish ovary, liver, gill and spleen after 30 min and 60 min acute hypoxia exposure. Meanwhile, the cortisol levels, white blood cells and several serum biochemical values of Korean rockfish under different oxygen concentration treatments were also detected. All the results might be helpful for further understanding of the potential effect of hypoxia in ovoviviparous fish. Highlights: Full length cDNAs of HIF-αs have been isolated from Sebastes schlegelii . We indicated an important role for HIF-αs during the acute hypoxia. S. schlegeli may be a good candidate for investigating ovoviviparous fish hypoxia tolerance mechanisms.